The limitation of the production of olive oils by the Spanish state - Latorre Ruiz, Juan (Przegląd Prawa Rolnego, 2021)
The instability of prices of produce at the source of its production in the agri-food sector presents a rather complicated situation. However, regarding the last link in the chain, namely marketing, the situation is quite different and this sector usually makes a profit on the sale of agricultural products. In Spain, the olive oil sector repeatedly suffers from this type of imbalance. Given these circumstances, the legislator has chosen to adopt, by means of a Royal Decree, some basic regulations that allow withdrawal of a certain production from the market in an orderly manner to alleviate the precarious situation, especially in terms of prices. This was done based on the European Union Regulation. In this article, the question that is asked is whether the operation of this regulation might lead to the distortion of the free market competition, or whether, perhaps, it may help to stabilise the prices at the source (original) production in the olive sector and thus protect the consumers.